Neoadjuvant Immuno-Chemotherapy: A New Perspective for Stage III NSCLC? - Yao, Yuanshan; Tang, Dongfang; Gao, Wen; Zhang, Huibiao (Frontiers in Surgery, 2022)
Background Stage III Non-small cell lung cancer (NSCLC) is a heterogenous disease with novel treatment options. Recently, immunotherapy has attracted a lot of attention for advanced NSCLC. Objective The objective of our study was to assess the efficacy and safety of neoadjuvant immuno-chemotherapy for resectable stage III NSCLC. Methods We analyzed 11 stage III primary NSCLC surgical cases who had undergone standard lobectomy or bronchial sleeve resection and lymph node dissection between December 2020 and July 2021. The data analyzed included basic clinical features, serum levels of key biomarkers, clinical efficacy in the perioperative period, postoperative pathological results, postoperative complications and the incidence rates of Immune-Related Adverse Events. Results Eleven patients were enrolled in our study with a mean age of 67.7 ± 4.8years, and 10 patients being men with former or current smoking history. Squamous carcinoma (10/11, 91.1%) was the most common cancer type. Six patients had stage IIIa, four had stage IIIb and one had stage IIIc. All patients received two or three cycles of neoadjuvant immuno-chemotherapy, with the median duration between the last treatment and surgery being 39 days (range, 32-46 days). All patients underwent R0 resection with ten patients undergoing single-port video-assisted thoracoscopic surgery. The surgeries took long because all the patients had extensive thoracic adhesions. Only three (3/11, 27.3%) patients experienced mild postoperative complications and none of the patients was hospitalized for long. Nine (9/11, 81.8%) patients experienced major pathological response of which seven (7/11, 63.6%) was complete pathological response in postoperative results. The pathological stage was downgraded in ten (10/11, 91.1%) patients, and although the incidence of Immune-Related Adverse Events was slightly higher (8/11, 72.7%), most events were grade 1-2 and did not delay surgery. Conclusion Our study demonstrated that neoadjuvant immuno-chemotherapy is feasible and relatively safe for resectable stage III primary NSCLC patients. We hope this new neoadjuvant immuno-chemotherapy model can improve overall survival and open a new era for stage III primary NSCLC patients.